Geophysical data from the Lockne Structure, Jämtland, Sweden - Sturkell, Erik; Ormö, Jens; Austin Hegardt, Eric; Stockmann, Gabrielle; Meland, Erik; Wikström, Torbjörn (University of Gothenburg, 2023)
Resistivity data
The resistivity data were collected with an ABEM Terrameter LS-CVES instrument along eleven profiles of variable length from 400 m to 1600 m. The distance between the electrodes was 5 m and a roll along strategy was adapted for longer profiles than 400 m. To correct for the effect of topography each profile was levelled by using a Sokkisha C3E. Profiles close to a benchmark altitude point from the Geodetic Survey of Sweden get correct absolute values, but for most of the profiles a perfect tie to a benchmark point was not possible. In these cases, the Lidar-height model was used. However, the relative height differences along all profiles are correct with centimetre precision. The resistivity measurements were performed during the summers 2013 to 2016 by Erik Sturkell, Jens Ormö, Eric Hegardt, Gabrielle Stockmann, Erik Meland, Åsa Frisk and Pierre Etienne Martin.
Data processing was made with the software Res2Dinv version 3.5 from Geotomo Software and the result is presented in a pseudo section. Data for the Res2Dinv processing, the number of iterations runed and what the absolute error are given in supplementary information table S02 (which is also included in the repository).
After the processed resistivity data were corrected for the topography, the results are presented in pseudo profiles along with interpretations shown in Figure 5a-c (main article), and additional data are available in the Supplementary information (which is also included in the repository). The processed resistivity data were sorted into ranges and connected to respective lithology. To present a calculation and inversion of electrical measurements as function of position (x, y, z) and electrode separation, the apparent resistivity is presented in a so called pseudo section.

Motståndsmätningar
Motståndsdata insamlades med ABEM Terrameter LS-CVES längs profiler av varierande längder, 400 m till 1600 m. Avståndet mellan elektroderna var 5 m och en "roll along"-metod tillämpades för profiler längre än 400 m. Precisionsavvägning genomfördes längs profilerna för att kunna genomföra en topografisk korrektion. För avvägningen användes avvägningsinstrumentet Sokkisha C3E.
Geofysiska data från Lockne-strukturen, Jämtland, Sverige
Keywords: EARTH SCIENCE; geophysics; geofysik; Geology; Geologi; Geophysics; Geofysik